The First Large Balloon Launch from Antarctica - Ground, John; Dallas, Kenneth; Cowie, Ralph; Thorn, Willard F. (1988)
This collection of five papers discusses the many practical problems, logistics, metrological planning, flight history and recovery operations for the first very large (11.6M cu ft) stratospheric balloon launched from Antarctica. The on-board Gamma Ray Advanced Detector (GRAD) was flown successfully to detect gamma ray emissions from Supernova 1987A. The 2500-lb payload was recovered from a 12,500-ft plateau by LC-130 aircraft. The instrumentation for command-control and telemetry, payload integration and testing, and the telemetry station installed aboard an LC-130 aircraft are described. An overview of the performance of the ARGOS satellite tracking and data-recovery system on this flight is included.